Does implicit mentalizing involve the representation of others' mental state content? Examining domain-specificity with an adapted Joint Simon task - Malcolm K. Y. Wong; Marina Bazhydai; Calum Hartley; J. Jessica Wang (Royal Society Open Science, 2024)
Implicit mentalizing involves the automatic awareness of others’ perspectives, but its domain-specificity is debated. The Joint Simon task demonstrates implicit mentalizing as a Joint Simon effect (JSE), proposed to stem from spontaneous action co-representation of a social partner's frame of reference in the Joint (but not Individual) task. However, evidence also shows that any sufficiently salient entity (not necessarily social) can induce the JSE. Here, we investigated the content of co-representation through a novel Joint Simon task where participants viewed a set of distinct images assigned to either themselves or their partner. Critically, a surprise image recognition task allowed us to identify partner-driven effects exclusive to the Joint task-sharing condition, versus the Individual condition. We did not observe a significant JSE, preventing us from drawing confident conclusions about the effect's domain-specificity. However, the recognition task results revealed that participants in the Joint task did not recognize their partner's stimuli more accurately than participants in the Individual task. This implies that participants were no more likely to encode content from their partner's perspective during the Joint task. Overall, this study pushes methodological boundaries regarding the elicitation of co-representation in the Joint Simon task and demonstrates the potential utility of a surprise recognition task.